2018
DOI: 10.2217/nnm-2018-0189
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Nanoceria: New Roles for an Old Player

Abstract: The use of different biomaterials with the ability to accelerate the repair and regeneration processes is of great importance in tissue engineering strategies. On this point, cerium oxide nanoparticles (CNPs or nanoceria) have recently attracted much attention due to their excellent biological properties including anti-oxidant, anti-inflammation and antibacterial activities as well as high angiogenic potential. The results of incorporation of these nano-sized particles into various constructs and scaffolds des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 129 publications
0
57
0
1
Order By: Relevance
“…Although there are studies on NC compatibility in cell and animal models, no data exist about the effects of NC on human hemostatic system. A recent study, performed in mice, showed that intratracheal instillation of NC promoted thrombosis in vivo , probably as consequence of increased oxidative stress and inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are studies on NC compatibility in cell and animal models, no data exist about the effects of NC on human hemostatic system. A recent study, performed in mice, showed that intratracheal instillation of NC promoted thrombosis in vivo , probably as consequence of increased oxidative stress and inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that NC, acting as ROS scavengers, are able to mimic the activity of SOD and catalase . According to their important intrinsic antioxidant and autoregenerative properties, NC applications have attracted increasingly interest in different fields of medicine . NC have been evaluated in vivo for their efficacy as treatment in a variety of disease states, with applications ranging from reproductive, to gastrointestinal, to ophthalmologic, to neurological and cardiovascular health .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerium oxide nanoparticles are synthesized by two kinds of approaches: the chemical methods and the green‐based methods …”
Section: Inorganic Nano‐antioxidants For Biomedical Applicationsmentioning
confidence: 99%
“…With the emergence of nanotechnology, smaller sizes of metals (1-100 nm) were evaluated by scientists to exactly determine their advantages and disadvantages for living systems, as nano-sized particles exhibit distinct biological effects in comparison to their bulk counterparts [ 3 , 4 ]. Among different types of nano-metals, cerium oxide nanoparticles (CNPs or nanoceria) are considered one of the most promising substances in biomedical engineering approaches [ 5 ].…”
Section: Introductionmentioning
confidence: 99%